Evaluation of the rehabilitation program for persons with complete paraplegia at Netcare rehabilitation hospital - Henn, M. J.; Mji, Gubela; Visagie, Surona (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Interdisciplinary Health Sciences. Speech-Language and Hearing Therapy))--University of Stellenbosch, 2009.